Masalah Penguasaan Kosa Kata Asas Bahasa Melayu dalam kalangan Murid Tahun 1 Sekolah Kebangsaan (Jurnal Bahasa, 2002)
This article looks into the problem of the basic proficiency in the Malay vocabulary among the students in Year One in a primary school. The study indicates that students can only master the alphabet satisfactorily while in the syllable stage, words, pharase and sentences, the students tend to be less proficient.